The complete mitochondrial genome of Omei Treefrog (Rhacophorus omeimontis). Issue 1 (2nd January 2020) - Fu, Changkun; Wang, Qian; Hu, Tao; Lei, Ziyong; Fan, Hailin; Zhao, Tianmeng; Zong, Hao
Abstract: In this study, the complete mitochondrial genome of Rhacophorus omeimontis was obtained and described. The sequenced mitogenome is total 19, 604 base pairs (bp) in length, which contained 13 protein-coding genes (PCGS ), 22 transfer RNA genes (tRNA), 2 ribosomal RNA genes (rRNA), and 2 control regions (D-loop). The overall base composition of the mitochondrial DNA is 32.5% for A, 30.5% for T, 23.3% for C, and 13.7% for G, and the percentage of GC content is 37.0%. The complete mitochondrial genome information of R. omeimontis will contribute to revealing the phylogenetic relationships among species of family Rhacophoridae.